A plausible involvement of plasmalemmal voltage‐dependent anion channel 1 in the neurotoxicity of 15‐deoxy‐Δ12, 14‐prostaglandin J2. Issue 12 (16th November 2020) - Koma, Hiromi; Yamamoto, Yasuhiro; Okamura, Noboru; Yagami, Tatsurou
Abstract: Introduction: 15‐deoxy‐Δ 12, 14 ‐prostaglandin J2 (15d‐PGJ2 ) causes neuronal apoptosis independently of its nuclear receptor, peroxysome‐proliferator activated receptor γ. Its membrane receptor, chemoattractant receptor‐homologous molecule expressed on Th2 cells (CRTH2), did not also mediate the neurotoxicity of 15d‐PGJ2 . In the present study, we ascertained whether membrane targets beside CRTH2 were involved in the neurotoxicity of 15d‐PGJ2 . Methods: Neuronal membrane targets for 15d‐PGJ2 were separated by two‐dimensional electrophoresis, identified by proteomic approach. Their localizations were detected by microscopic immunofluorescence study. Cell viability and apoptosis was evaluated by MTT‐reducing activity and caspase‐3 activity, respectively. Results: Voltage‐dependent anion channel 1 (VDAC1) was identified as one of membrane targets for 15d‐PGJ2 . Modification of VDAC1 with 15d‐PGJ2 was detected by pull‐down assay. VDAC1 was detected in the plasma membrane and localized on the neuronal cell surface. VDAC1 was partially colocalized with membrane targets for 15d‐PGJ2 . The anti‐VDAC antibody significantly attenuated the neurotoxicity of 15d‐PGJ2, accompanied by the suppression of the 15d‐PGJ2 ‐stimulated caspase‐3. Conclusion: These findings suggested that the plasmalemmal VDAC might be involved in the neurotoxicity of 15d‐PGJ2 . Abstract : By proteomic analysis, we identified plasmalemmal voltage‐dependent anion channel (pl‐VDAC) as one of membrane targets for 15d‐PGJ2 . An anti‐VDAC antibody suppressed the neurotoxicity of 15d‐PGJ2 partially, but significantly, suggesting that pl‐VDAC might contribute to the neurotoxicity of 15d‐PGJ2 .